1956
DOI: 10.1143/ptp.16.320
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Deformability and Shell Structure

Abstract: The connection between the surface rigidity of the nuclear core, which has been accounted for in tenns of the surface tension of liquid drop nuclei, and its proper shell structure is discussed by using the method of the quantum mechanical description of the collective motion, which has been proposed by one of the present authors and others (§ 2). On the basis of such a consideration the surface rigidity of the core can be calculated, provided that the shell model is valid for the behaviour of particles forming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0

Year Published

1957
1957
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 4 publications
0
47
0
Order By: Relevance
“…It should be noted that the rigidity of 48 Ca is higher than one of the 40 Ca and reaches the maximal value for the nuclei with A < 50 -C( 48 Ca) ≈ 800 MeV. It should be noted that the ratio of rigidities of Ca isotopes extracted from the data on the mean-square deformations, does not agree with the corresponding results of the collective model calculations [7]. The latter, based on a specified scheme for quantum numbers and energy levels, have concluded that C( 40 Ca) > C( 48 Ca).…”
mentioning
confidence: 79%
“…It should be noted that the rigidity of 48 Ca is higher than one of the 40 Ca and reaches the maximal value for the nuclei with A < 50 -C( 48 Ca) ≈ 800 MeV. It should be noted that the ratio of rigidities of Ca isotopes extracted from the data on the mean-square deformations, does not agree with the corresponding results of the collective model calculations [7]. The latter, based on a specified scheme for quantum numbers and energy levels, have concluded that C( 40 Ca) > C( 48 Ca).…”
mentioning
confidence: 79%
“…Due to the form factor (20), the forward peaks of angular distribution will slightly increase in comparison with the case of zero range nuclear force. The effect, however, may be negligible when the incident energy of neutron is below 5 Mev.…”
Section: Methods Of Approximation and Their Validitiesmentioning
confidence: 98%
“…:!l however, veff is dependent on the structure of the core through the collective eigen-&equencies, w1• This provides us with an explanation for the differences in the quadrupole moments of some isotopes. 6 > Secondly, the summation over n in (5 · 7) is usually carried out only for the main terms, and the applicability of configurational -mixing is restricted to the case of small perturbation. The same restriction holds in the collective model, in so far as the weak coupling approximation is employed.…”
Section: (6 · 3)mentioning
confidence: 99%
“…Thirdly, our method is different from the current collective model of A. Bohr.l7) In the latter case w 1 is determined on the basis of the hydrodynamical mode', whereas in our case w1 is obtained from the collective motion for a given rigidity which depends strongly upon the structure of the core. 6 where pP(x) is the density of protons and…”
Section: (6 · 3)mentioning
confidence: 99%
See 1 more Smart Citation